2021
DOI: 10.3390/membranes11110817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Membrane Phosphoric Acid Doping Level on Transport Phenomena and Performance in High Temperature PEM Fuel Cells

Abstract: In this work, a three-dimensional mathematical model including the fluid flow, heat transfer, mass transfer, and charge transfer incorporating electrochemical reactions was developed and applied to investigate the transport phenomena and performance in high-temperature proton exchange membrane fuel cells (HT-PEMFCs) with a membrane phosphoric acid doping level of 5, 7, 9, 11. The cell performance is evaluated and compared in terms of the polarization curve. The distributions of temperature, oxygen mass fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…New membranes should be developed with high proton conductivity networks, with, for instance, ionic clusters on the membrane surface [341]. In addition, a trade-off may need to be reached between a membrane with intrinsically high proton conductivity and high doping and retention capabilities, as these drive different membrane synthesis approaches [342]. Recently developed cross-linked membranes synthesized based on poly(ethylene imine) (PEI) and poly(ether ketone cardo) should be explored further, as the abundant PEI amino groups provide superior PA absorption capability and conductivity for these membranes [343].…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…New membranes should be developed with high proton conductivity networks, with, for instance, ionic clusters on the membrane surface [341]. In addition, a trade-off may need to be reached between a membrane with intrinsically high proton conductivity and high doping and retention capabilities, as these drive different membrane synthesis approaches [342]. Recently developed cross-linked membranes synthesized based on poly(ethylene imine) (PEI) and poly(ether ketone cardo) should be explored further, as the abundant PEI amino groups provide superior PA absorption capability and conductivity for these membranes [343].…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…The mixture of the acid-base membrane allows for high thermal and chemical stabilities, in addition to a proton conductivity in the same range as, or even higher than, that of Nafion. Among the strong acids, phosphoric acid (H 3 PO 4 ) and sulphuric acid (H 2 SO 4 ) show valuable proton conductivities in both wet and anhydrous forms [24,25]. PBI is known for its high chemical and thermal stability.…”
Section: Proton Exchange Membrane Fuel Cells (Pemfcs)mentioning
confidence: 99%
“…There are many numerical studies related to HT-PEMFCs in the available literature. Li et al [ 7 ] studied effect of membrane phosphoric acid doping level on transport characteristics and cell performance. It was reported that cell performance is increased with the increase in doping level.…”
Section: Introductionmentioning
confidence: 99%